2015
DOI: 10.1016/j.chom.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Chemodetection and Destruction of Host Urea Allows Helicobacter pylori to Locate the Epithelium

Abstract: SUMMARY The gastric pathogen Helicobacter pylori interacts intimately with the gastric mucosa to avoid the microbicidal acid in the stomach lumen. The cues H. pylori senses to locate and colonize the gastric epithelium have not been well defined. We show that metabolites emanating from human gastric organoids rapidly attract H. pylori. This response is largely controlled by the bacterial chemoreceptor TlpB, and the main attractant emanating from epithelia is urea. Our previous structural analyses show that Tlp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
141
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(154 citation statements)
references
References 50 publications
(65 reference statements)
3
141
0
Order By: Relevance
“…A few years earlier, TlpB was shown to have a tightly bound urea molecule that functions as a cofactor for pH sensing (Goers Sweeney et al, 2012). This observation led Huang et al (2015) to test whether urea was the molecule produced by the gastric organoidsas well as by many other mammalian cells-and indeed, it was.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…A few years earlier, TlpB was shown to have a tightly bound urea molecule that functions as a cofactor for pH sensing (Goers Sweeney et al, 2012). This observation led Huang et al (2015) to test whether urea was the molecule produced by the gastric organoidsas well as by many other mammalian cells-and indeed, it was.…”
mentioning
confidence: 96%
“…The chemoreceptor responsible for detecting urea, however, was not known. To analyze which chemoreceptors are relevant to sense metabolites produced by human stomach cells, Huang et al (2015) utilized human gastric organoids and asked what H. pylori attractant chemicals are released by them and which chemoreceptors sense them ( Figure 1). They obtained a strong attractant signal that mapped to one of H. pylori's four chemoreceptors, TlpB.…”
mentioning
confidence: 99%
“…The chemotactic activities exhibited by H. pylori presented in response to urea suggest that the proton motive force generated in the process is adequate for swimming in chemotaxis buffer. As discussed, adaptive mechanisms are responsible for the chemotactic movement toward attractants [30,33]. In H. pylori, chemoattractant sensing is mediated by methyl-accepting chemotaxis proteins (MCP), which contain a large cytoplasmic signaling and adaptation domain.…”
Section: Impact Of Urea On the Type And Frequency Of H Pylori Movementsmentioning
confidence: 99%
“…Mounting evidence suggests that signaling through all four chemoreceptors is necessary for efficient colonization of the gastric epithelium (45). It has been shown that H. pylori exhibits chemotaxis toward metabolites emanating from the human gastric epithelium and that urea is the primary host-derived metabolite that attracts the bacterium (46). Urea is sensed by TlpB, and its very high affinity enables responses to concentrations as low as 50 nM.…”
mentioning
confidence: 99%